Case report: A preterm infant with rubinstein-taybi syndrome and Marmorata telangiectatica harboring a frameshift mutation in the CREBBP gene - Yang, Yang; Xiao, Jing; Ye, Yuanyuan; Xiang, Jianwen; Wang, Zhu; Chen, Jia (Frontiers in Pediatrics, 2023)
Rubinstein-Taybi syndrome (RSTS) is a rare autosomal dominantly inherited disease characterized by slow mental and physical growth, skeletal abnormalities (broad thumbs and big toes), and dysmorphic facial features. RSTS is associated with de novo variants of the epigenetic-associated gene CREBBP. RSTS is primarily diagnosed based on clinical manifestations and genetic testing. Cutis marmorata telangiectatica congenita (CMTC) is a rare, congenital, and typically benign vascular anomaly of unknown etiology; it is described as persistent reticulated marbled erythema. The diagnosis of CMTC is largely based on clinical features, and GNA11 mutations are associated with CMTC. In this case report, we describe the case of a preterm infant (boy) with RSTS and CMTC who had a novel frameshift mutation leading to a premature stop codon in the CREBBP gene. This study adds the novel mutation c.5837dupC to the known molecular spectrum of disease-causing CREBBP gene mutations.